(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Ulcer is a common disorder in oral mucosa and gastrointestinal. Number of synthetic drugs are available to treat ulcers but these drugs have undesirable side effects. The present study aimed to investigate Preliminary screening of Mimosa pudica Linn seeds for oral and stomach ulcers. Plant material of both plants were extracted with different organic solvents and yield was calculated. Preliminary phytochemical tests were applied for the detection of presence of different chemical constituents in petroleum ether, chloroform, ethyl acetate, ethanol and aqueous extracts. All these extracts were also screened for anti-ulcer effect on ethanol induced stomach ulcer and glacial acetic acid oral ulcer. The effect was observed by the measurement of ulcer index, percentage inhibition, pH Total acidity, and gastric volume. Biochemical assessment of antioxidant substances and pro-inflammatory mediators (TNF-α, IL-6 and PGE-2) were done in the mucosal tissues. Phytochemical screening revealed the presence of steroids, terpenoids, and fatty acid in petroleum ether and alkaloids, tannins and phenolic compounds in chloroform extract of M. pudica Linn seeds the ethyl acetate and ethanol extract contain flavonoids, tannins and phenolic compounds, glycosides. Results of Preliminary pharmacological screening was showed that ethanolic extract of M. pudica Linn seeds with 200 and 400 mg/kg b.w. dose have significant anti-ulcer potential and is comparable to the standard (Omeprazole and ORASORE Gel). The significant restoration of antioxidant substance and inflammatory mediators indicated supporting mechanism of ulcer healing of ethanolic extract. In conclusion, the anti-ulcer effects were showed in dose-dependent manner. The potential anti-ulcer effect may be due to presence of flavonoid components i.e., quercetin, luteolin, etc. in the ethanolic extract of M. pudica Linn seeds.